2010
DOI: 10.1128/jvi.00747-10
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 Protease Has a Genetic T-Cell Adjuvant Effect Which Is Negatively Regulated by Proteolytic Activity

Abstract: HIV protease (PR) mediates the processing of human immunodeficiency virus (HIV) polyproteins and is necessary for the viral production. Recently, HIV PR was shown to possess both cytotoxic and chaperonelike activity. We demonstrate here that HIV PR can serve as a genetic adjuvant that enhances the HIV Env and human papillomavirus (HPV) DNA vaccine-induced T-cell response in a dose-dependent manner, only when codelivered with DNA vaccine. Interestingly, the T-cell adjuvant effects of HIV PR were increased by in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…29 Additionally, the inactivated HIV-1 protease acts as a strong T-cell adjuvant for genetic vaccines exerting an antitumor effect in a HPV cancer mouse model. 30 It is suggested that antigens expressed during the first phase of growth initially provide protection against M. tuberculosis infection, whereas those expressed during the late stages help to prevent reactivation of the disease. 4 The protective effects of early secreted culture filtrate proteins, including ESAT-6, TB10.4, Ag85A and Ag85B, are well established.…”
Section: Discussionmentioning
confidence: 99%
“…29 Additionally, the inactivated HIV-1 protease acts as a strong T-cell adjuvant for genetic vaccines exerting an antitumor effect in a HPV cancer mouse model. 30 It is suggested that antigens expressed during the first phase of growth initially provide protection against M. tuberculosis infection, whereas those expressed during the late stages help to prevent reactivation of the disease. 4 The protective effects of early secreted culture filtrate proteins, including ESAT-6, TB10.4, Ag85A and Ag85B, are well established.…”
Section: Discussionmentioning
confidence: 99%